Using intra-microgel crosslinking to control the mechanical properties of doubly crosslinked microgels. Issue 33 (1st August 2016) - Cui, Zhengxing; Wang, Wenkai; Obeng, Melody; Chen, Mu; Wu, Shanglin; Kinloch, Ian; Saunders, Brian R.
Abstract : The ductility of hydrogels constructed from covalently interlinked microgels is shown to be controlled by the crosslinking monomer used to prepare the microgel. Abstract : Microgels (MGs) are crosslinked polymer particles that swell when the pH approaches the p K a of the constituent polymer. Our earlier work showed that concentrated MG dispersions can be covalently interlinked to form macroscopic hydrogels, which are termed doubly crosslinked microgels (DX MGs). Here, we study for the first time the effects of intra-MG crosslinking on the swelling of the MGs and the mechanical properties of the DX MGs. The MGs were synthesised by emulsion copolymerisation of ethyl acrylate (EA) or methacrylic acid (MAA) and divinylbenzene (DVB). The latter was a crosslinking monomer. For comparison, MGs were prepared where DVB was replaced by either 1, 4-butanediol diacrylate (BDDA) or a 1 : 1 mixture of both DVB and BDDA. The MG swelling behaviours were studied by dynamic light scattering; whereas, the DX MG mechanical properties were studied by dynamic rheology and uniaxial compression measurements. Inclusion of DVB within the MGs resulted in both highly swelling MGs and highly ductile DX MGs. The average strain-at-break value for the DVB-containing DX MGs was 76% which represents the highest value yet reported for a DX MG prepared using commercially available monomers. It was also shown that good tuneability of the DX MG properties could be obtained simply by controlling the DVB and BDDA contents within the MG particles. Analysis of the swelling and compression data enabled relationships between the volume-swelling ratio of the MGs and either the modulus or strain-at-break values for the DX MGs. These relationships also applied to a DVB-free system prepared with a low BDDA content. An interesting conclusion from this study is that the DX MGs can be thought of mechanically as macroscopic MG particles. The results of this study provide design tools for improving DX MG ductility and hence increasing the range of potential applications for this new class of hydrogel.